"O Acaba Mundo já era": o ocultamento dos cursos d'água no centro de Belo Horizonte (1893-1973) - Wallace Carrieri de Paula Andrade (2014)
This research addresses different stages of transformation in the landscape of the central area of Belo Horizonte, since its city plan, conceived and designed in the late nineteenth century until the mid-twentieth century, encompassing the major urban interventions that fall on the water. We investigated the influence that hydrographic city pathways exercised in the choice of site, the political-administrative ideal due to which the water courses were modified and adapted and the implications of these changes in the relationship of the inhabitants with water. From a dialogue with historical sources related to construction processes and intervention in Belo Horizonte, we seek to compose a framework for possible disqualification and see the systematic concealment of the watercourse as one of the elements that make up the urban landscape